The Association between Acne Vulgaris and Stress among Adolescents in Kenjeran, Surabaya - Zsa Zsa Ollyvia; Nining Febriyana; Damayanti Damayanti; I Gusti Ayu Indah Ardani (Jurnal Psikiatri Surabaya, 2021)
Background: Acne vulgaris is the main skin disease problem for adolescents. The complication of acne in adolescents is scars left on the face, which affects stress levels. Stress has harmful potential when the conditions exceed the individual's ability to cope. Kenjeran area has a tropical climate and weather which are the factors that cause acne vulgaris. Objective: This research aims to study the association between acne vulgaris severity and stress among adolescents in Kenjeran, Surabaya Methods: This research used non-probability purposive sampling technique and observational analytic method with cross-sectional design. Assessment of the acne severity was carried out by dermatologist using Lehmann’s Grading System and stress levels were assessed using the Perceived Stress Scale questionnaire in 109 adolescent subjects. Results: The highest frequency is women aged 15 years. The dominance is in mild acne severity with moderate stress. It was found that adolescents with acne vulgaris are at risk of experiencing stress even though the analysis of the results using fisher-exact showed that there was no significant association between the acne severity and stress level in adolescents with acne vulgaris (p=0.113). Conclusion: The presence of acne vulgaris puts adolescents at risk of experiencing mild, moderate, or severe stress. It requires attention because can cause adverse effects that affect adolescents into adulthood life.